Tren penggunaan metode penelitian pendidikan pada Jurnal Internasional - Asep Abdurrohman (ADPISI (Asosiasi Dosen Pendidikan Agama Islam Se-Indonesia), 2024)
The use of methods and origins of researchers in international journals is very diverse. Both journals published in the western and eastern parts of the world. This research aims to examine trends in the use of methods and researchers' origins in international journals through the Education Resources Information Center (ERIC) media as the search center. In ERIC, there are two journals studied by researchers, namely the European Journal of Educational Research (EU-JER) which has 30 journals and the Turkish Online Journal (TOJ) which has 29 journals. To study it, researchers used Content Analysis. Content Analysis is a scientific analysis of the message content of a communication. Technically, the scope of content analysis includes; classification of signs used in communication, using criteria as a basis for classification, and using certain analytical techniques as a prediction maker. There are three conditions in content analysis, namely; objectivity, systematic approach, and generalization. The research results show that the trend in using research methods in the European Journal of Educational Research (EU-JER) is 50% using qualitative methods. Meanwhile, in TOJ, the trend in using research methods is the opposite of EU-JER, namely 48% quantitative. Meanwhile, 100% of the researchers at EU-JET come from Indonesia. Meanwhile, in TOJ the authors are a mixture of domestic and foreign writers. Domestically 69% and overseas 31%.